Pengaruh Pendekatan Value Clarification Technique (VCT) dalam Pembelajaran Sejarah terhadap Motivasi Belajar Siswa Kelas XI IPS 3 SMA Negeri 1 Kuantan Mudik - Mairika Purnama; Bunari Bunari; Suroyo Suroyo (Universitas Hamzanwadi, 2023)
This research is motivated by the fact that teachers in learning still use conventional methods and only focus on the teacher so that students are less active, less interesting, and boring for students and they do not have strong motivation to learn. The aims of this research are; to determine the effect of using the Value Clarification Technique (VCT) approach on students' learning motivation in class IPS 3 SMA Negeri 1 Kuantan Mudik. This research uses quantitative methods with the type of Quasi-Experimental Design research or quasi-experiment with product moments. The results of this research show that there is an influence of using the VCT approach on student learning motivation where sig (2-tailed) is 0.00 < 0.05, meaning that Ha is accepted, and Ho is rejected. The large influence of using the VCT approach on student learning motivation can be seen from the average questionnaire score in the control class with a pretest score of 69.42 and a post-test of 75.42, while for the experimental class, the pretest score was 68.96 and the post-test increased to 80.69.